Consórcio milho-plantas de cobertura e viabilidade técnica da soja safrinha - Salomão, Everton Carlos (2017)
One of the greatest challenges for the current productive systems is to maintain or increase productivity per area with lower inputs being the consortium between commodities, such as soybean and maize, with forage species and/or cover crops an alternative. Moreover, integrated production systems are more complex due to the interactions that occur among its components. In this context, the present work aimed to evaluate the intercropping of corn with cover crops at the main and second summer crop willing to understand how these systems can be used in the crop-livestock farmers. It is also known that soybean plays an important role in crop rotation and is an excellent source of income for farmers, it was sought to study cropping systems in which it is possible to grow soybeans within the allowed sowing data established for the crop in the southwest of Paraná. The study is divided into three studies: Study I: Corn and forage yield in the intercropped system with forage species; Study II: Development and corn yield grown in a consortium with cover species, and biomass accumulation potential of these species; Study III: Production potential of silage and grains of corn hybrids with different cycles, and soybean yield in the second summer crop under these areas. The studies were carried out at the Universidade Tecnológica Federal do Paraná - Câmpus de Dois Vizinhos, during the 2015/2016 crop season and the second summer crop in 2016. Study I (crop) and Study II (second crop) was carried out using corn hybrid 30F53YH intercropped with Crotalaria spectabilis, Cajanus cajan, Urochloa brizantha and Urochloa ruziziensis in 45 cm spacing between corn rows. In these studies, the green and dry mass productive potential of corn crop and cover crops were evaluated. Bromatological quality of the silage from these production systems was also evaluated. Sorghum (Sorghum bicolor) was used to compare the yield of biomass after corn silage in relation to the treatments cultivated in consortium with Urochloa brizantha and Urochloa ruziziensis. In Study III, 30F53YH and P1680YH hybrids were evaluated for silage and grain yield and after it, soybean was grown as a second crop, evaluating yield components and its yield potential. It was noticed that corn intercropped with Urochloa brizantha, Urochloa ruziziensis, Crotalaria spectabilis and Cajanus cajan at the study I did not affect the development of corn plants, neither its morphological and yield components characteristics resulting in similar yield as the crop grown alone, with an average grain yield of 10.756 kg ha-1. Also, in Study I, it was observed that the accumulation of biomass for silage, of the corn crop, is higher in the single crop (67.290 kg ha-1) in relation to the treatments under consortium. Among the species cultivated in consortium, the use of Urochloa ruziziensis results in a greater accumulation of dry biomass, with a yield of 1.084 kg ha-1 of dry mass. Silage from corn crop grown alone showed similar bromatological quality in relation to the treatment under consortium, except for neutral detergent fiber values, which are different, showing value of 33,82 and 37,1 respectively for the treatment with corn alone and intercropped with Urochloa ruziziensis. Cultivation of sorghum (Sorghum bicolor) as a second summer crop, after corn silage results in a greater accumulation of biomass under the same area (47.834 kg ha-1 of dry mass), differing in relation to Urochloa brizantha and Urochloa ruziziensis, which accumulated respectively 29.917 and 32.089 kg ha-1 of total dry mass. In the second crop, the highest production of dry biomass among the intercropping species is observed for the treatment using Urochloa ruziziensis (1.546 kg ha-1). On the other hand, the morphological characteristics of corn plants and yield components show differences for intercropping and corn cultivated alone. The yield of maize in the second crop was reduced when it was cultivated in a consortium with Urochloa ruziziensis, yielding 7.662 kg ha-1. Corn hybrid 30F53YH with early cycle, showed higher green (67.290 kg ha-1) and dry mass (19.481 kg ha-1) biomass for silage, and so for grain yield (11.195 kg ha-1), in relation to the hybrid P1680YH with a shorter cycle. As the hybrids were for silage and grain production, and presented different cycles, they resulted in four soybean sowing periods, being: 17/12/2015 for soybean on corn P1680YH silage, 01/01/2016 for soybean on corn 30F53YH, 17/01/2016 for soybeans on corn grain P1680YH and 01/29/2016 for soybeans on corn grain 30F53YH. It was noticed that corn hybrid grain P1680YH cultivated for silage, allows farmers to cultivate soybean as a second summer crop inside the sowing data established for the crop in the southwest of Paraná. Soybean yield reduces as sowing is delayed, being observed yields of 3.490 kg ha-1 for sowing on 12/17/2015 and 2.681 kg ha-1 for sowing on 01/29/2016. All the evaluated systems shows advantages to the production systems, being viable alternatives to the farmer, depending on the species used, time of sowing and production system realized, being possible to integrate the grain production with the cattle raising, or even providing a contribution of biomass for soil protection and conservation.